2000
DOI: 10.1074/jbc.m003555200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AP1 (Jun/Fos) Factor Expression and Activation in Ovarian Granulosa Cells

Abstract: Growth of ovarian follicles involves regulated proliferation and differentiation of granulosa cells (1, 2). Exponential growth of granulosa cells in preovulatory follicles is followed by their terminal differentiation and formation of the corpus luteum, a transition initiated by the ovulatory surge of luteinizing hormone (LH).1 This transition of proliferating granulosa cells to non-dividing luteal cells is associated with specific changes in the expression of cell cycle regulatory molecules that control speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(76 citation statements)
references
References 47 publications
6
67
0
1
Order By: Relevance
“…The results demonstrated that endogenous p53 protein interacts directly with predicted p53 binding sequences in these 5 genes, and that in silico prediction can greatly assist us in focusing on regions likely to confer p53-mediated expression. The biological properties of these genes are consistent with the functions that have been attributed to p53, such as, cell cycle checkpoints, apoptosis, inhibition of angiogenesis, and genetic stability (2,(23)(24)(25). The data suggest that these genes could be mediators of p53 expression through transcriptional regulation.…”
Section: Fig 2 P53 Interacts With Predicted P53 Dna-binding Sites Isupporting
confidence: 63%
“…The results demonstrated that endogenous p53 protein interacts directly with predicted p53 binding sequences in these 5 genes, and that in silico prediction can greatly assist us in focusing on regions likely to confer p53-mediated expression. The biological properties of these genes are consistent with the functions that have been attributed to p53, such as, cell cycle checkpoints, apoptosis, inhibition of angiogenesis, and genetic stability (2,(23)(24)(25). The data suggest that these genes could be mediators of p53 expression through transcriptional regulation.…”
Section: Fig 2 P53 Interacts With Predicted P53 Dna-binding Sites Isupporting
confidence: 63%
“…In addition, steroid producing tissues are thought to require AP-1 for the regulation of steroidogenesis [387,[385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400]. AP-1 transcription factors are homo-and hetero-dimers of Jun (c-Jun, JunB and JunD), Fos (c-Fos, FosB, FosB splice variants FosB2 and DeltaFosB2 and Fra-1 and Fra-2) Jun dimerization partner (JDP1 and JDP2) and the closely related activating transcription factor (ATFa, ATF2, LRF1/ATF3, B-ATF) family of proteins characterized by basic region and leucine-zipper domains [353,385,[389][390][391][392][393][394].…”
Section: Ap-1 Transcription Factormentioning
confidence: 99%
“…2) is involved in the response to LH by the maturational events in mouse COC including cumulus expansion and oocyte meiosis resumption (GVBD; Su et al 2003). ERK1/2 is also suggested to phosphorylate several transcriptional factors implicated in the final maturation and the ovulation processes, including FOS, MYC, STAT3, and LH genomic effect on bovine cumulus cells AP1 (Sharma & Richards 2000, Roux & Blenis 2004, Russell & Robker 2007. AP1, for example (Fig.…”
Section: Cell Signalingmentioning
confidence: 99%